Sound Exchange. - WALZER, DANIEL (Leonardo Music Journal, 2015)
Affordable technology facilitates an immediate documentation of sound and space that encourages collective artistic expression modeled after track- or song-remixing websites. Students in a newly proposed music composition course must capture and generate original sounds, and then upload them to a separate class drive for other students to reuse. New creative work consists entirely of these reused sounds. The author discusses the use of remixed sound collages in an open access format and considers the positive influence of legal file exchange and remixing in educational musical practice.